2016
DOI: 10.5535/arm.2016.40.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Proper Robot-Assisted Gait Training Group in Non-ambulatory Subacute Stroke Patients

Abstract: ObjectiveTo identify the clinical characteristics of proper robot-assisted gait training group using exoskeletal locomotor devices in non-ambulatory subacute stroke patients.MethodsA total of 38 stroke patients were enrolled in a 4-week robotic training protocol (2 sessions/day, 5 times/week). All subjects were evaluated for their general characteristics, Functional Ambulatory Classification (FAC), Fugl-Meyer Scale (FMS), Berg Balance Scale (BBS), Modified Rankin Scale (MRS), Modified Barthel Index (MBI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
14
2
Order By: Relevance
“…(4) Functional Ambulation Category (FAC) scores: The FAC was used to assess gait ability, which was rated along six levels (scores ranging from 0 to 5) based on the amount of physical support required, regardless of whether an assistive device was used [35]. Balance function is a significant predictive factor for gait function [36]. A previous systematic review has indicated that balance and gait may share similar components that can be targeted using a single form of therapy [22].…”
Section: Methodsmentioning
confidence: 99%
“…(4) Functional Ambulation Category (FAC) scores: The FAC was used to assess gait ability, which was rated along six levels (scores ranging from 0 to 5) based on the amount of physical support required, regardless of whether an assistive device was used [35]. Balance function is a significant predictive factor for gait function [36]. A previous systematic review has indicated that balance and gait may share similar components that can be targeted using a single form of therapy [22].…”
Section: Methodsmentioning
confidence: 99%
“…Stroke usually causes impairments in variety of areas, such as cognition, emotion, motor, and sensory, and thereafter results in imbalance and gait disability as well as impairment of the activities of daily living (ADLs) [1]., Among those areas, poor balance control have an negative influence on the recovery of gait and motor function [2][3][4], even if motor recovery progresses to some extent [5]. Many therapeutic interventions, such as visual feedback training [6], robotic devices [7], mirror therapy [8], and motor imagery training [9] have been performed to improve balance control. Those methods have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The scoring on this scale varies from 0 to 6, with 0 indicating lack of incapacity and 6 indicating fatality. [23]…”
Section: Methodsmentioning
confidence: 99%